2019
DOI: 10.1097/md.0000000000014669
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital, short-term and long-term adverse clinical outcomes observed in patients with type 2 diabetes mellitus vs non-diabetes mellitus following percutaneous coronary intervention

Abstract: Background: Several studies have shown that patients with type 2 diabetes mellitus (T2DM) have worse clinical outcomes in comparison to patients without diabetes mellitus (DM) following Percutaneous Coronary Intervention (PCI). However, the adverse clinical outcomes were not similarly reported in all the studies. Therefore, in order to standardize this issue, a meta-analysis including 139,774 patients was carried out to compare the in-hospital, short-term (<1 year) and long-term (≥1 year) adverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 49 publications
1
19
0
2
Order By: Relevance
“…Regarding the angiographic profile, double vessel disease was the common angiography pattern and LAD was the most commonly involved vessel in both groups, which is consistent with previous studies [ 8 , 11 ]. The current study shows that DM patients are more at risk of adverse clinical outcomes after PCI, either during the hospital stay or at a one-year follow-up, which is similar to the findings of Zhuo et al [ 12 ]. In our study, stent thrombosis and contrast-induced nephropathy have been found to be higher in DM patients during their hospital stay, but at one year follow-up MACE, followed by stent thrombosis, were more in the non-DM group, which is in line with previous studies [ 12 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding the angiographic profile, double vessel disease was the common angiography pattern and LAD was the most commonly involved vessel in both groups, which is consistent with previous studies [ 8 , 11 ]. The current study shows that DM patients are more at risk of adverse clinical outcomes after PCI, either during the hospital stay or at a one-year follow-up, which is similar to the findings of Zhuo et al [ 12 ]. In our study, stent thrombosis and contrast-induced nephropathy have been found to be higher in DM patients during their hospital stay, but at one year follow-up MACE, followed by stent thrombosis, were more in the non-DM group, which is in line with previous studies [ 12 ].…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in line with Mathew et al [ 16 ]. Similarly, a study by Zhuo et al [ 12 ] also demonstrated worse outcomes in DM patients on follow-up. Kedhi et al [ 17 ] also reported a high number of deaths, MI, and stent thrombosis in the DM group after PCI, thus supporting our findings.…”
Section: Discussionmentioning
confidence: 74%
“…In the ODYSSEY OUTCOMES research, a more pronounced absolute risk reduction was observed in patients with polyvascular disease than monovascular disease (Jukema et al, 2019). As the traditional risk factors for adverse events, cost-effectiveness of alirocumab were calculated in pre-existing diabetes mellitus (DM) (Li et al, 2016;Zhuo et al, 2019) and hypertension population (Chen et al, 2009;De Luca et al, 2014) with MI, respectively. Other scenario analyses were also performed, including initiating treatment among patients in different ages, varying the duration of alirocumab use between 5 and 30 years and applying various discount rates to the model.…”
Section: Scenario Analysesmentioning
confidence: 99%
“…Coronary vessels in patients with diabetes usually present extensive atherosclerosis with a larger number of significant stenosis, longer lesions, and more diffuse disease 3 , 4 . Therefore, despite advances in interventional skill, devices, and antiplatelet agents, outcomes of coronary revascularization in patients with diabetes have been poorer than those without 5 , 6 . Percutaneous coronary intervention (PCI) in patients with diabetes is associated with increased incidence of restenosis, repeat revascularization, stent thrombosis (ST), and all-cause mortality than those without 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%